Samtale mellem religion og filosofi - Thomassen, Niels (Religionsvidenskabeligt Tidsskrift, 1995)
Universal philosophy of religion is occupied with religion as a human manifestation, its essence and its function in human life. Special philosophy of religion is entrusted with giving a rational elucidation of the teachings of a particular religion, e.g. christianity. the medieval philosophers operated in this way and so do modern philosophers of religion as Kierkegaard and Løgstrup. In principle there is no difference between philosophy of religion and philisophy of science. The tasks of christian philosophy of religion are of the same kind as the tasks of philosophy of science and humanities get from phychoanalytic interpretation of literature, semiotics or hermeneutical bioloy. Philosophy has difficulties in answering the problems which traditionally have been answered by religion. Philosophy is a confession to reason, but the totally rational world is a caricature. Philosophy and reason are not the highest forms of life, but ought to take up a serving function. therefore the paper concludes in a dichotomy between academic considerations and some unacademic aphorisms.